Reading Practices of Students of the Metropolitan Metropolis: “Amateurs” and “Pragmatists” - E. V. Kargapolova; V. V. Diakova; M. A. Simonenko; Ju. A. Davydova (Высшее образование в России, 2022)
Modern social processes (globalization, urbanization, digitalization, succession of generations and others) actualize public and scientific attention to students’ reading culture, reading practices and their various aspects (gender, social, economic, and others). The issue of culture of reading, reading practices, their features and structure is a topical and relatively under-developed topic of interdisciplinary analysis. These phenomena are considered in sociology within the framework of some concepts: as a separate type of practice in the process of personal literacy formation, through the connection of cultural heritage and social class, through the analysis of subjective and existential meanings of the reading experience, and others. It is interesting to study the reading practices of students due to the specificity of the subject-object role of this social group in the process of cultural intergenerational continuity. The article highlights the results of an empirical study conducted among students of Moscow universities. Two types of students’ attitudes to works of fiction are revealed: pragmatic and value-reflective. The characteristics of these two groups are given, compared with other indicators (love of reading, reading as pleasure, volume of reading, genres of fiction, and others). The main conclusions and results presented in the publication will be of interest to teachers, scientists, representatives of state and public organizations and specifically to students.